HUBUNGAN WAKTU TUNGGU DAN SIKAP PETUGAS DENGAN KEPUASAN PASIEN PADA INSTALASI FARMASI RUMAH SAKIT ISLAM SURABAYA (RSIS) JEMURSARI - Agus Aan Adriansyah; Ima Nadatien (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2019)
Introduction: Jemursari Surabaya Islamic Hospital has a Pharmacy Installation service that requires long prescription service waiting times. This resulted in the emergence of patient dissatisfaction with the quality of services available at the Jemursari Islamic Hospital Pharmacy Installation in Surabaya. In relation to patient satisfaction and the quality of service at the Jemursari Islamic Hospital, there are still patients who are dissatisfied with the services of the Jemursari Islamic Hospital Pharmacy Installation staff. This study aims to analyze the relationship between waiting time and the attitude of the officer with patient satisfaction at the Jemursari Islamic Hospital Pharmacy Installation in Surabaya. Method: this study was an observational analytic study using aapproach cross sectional. The research locations were in Depo 1 Pharmacy Installation, Jemursari Islamic Hospital, Jl Jemursari no. 51-57, Jemur Wonosari, Wonocolo, Surabaya City, East Java. The research sample was 100 respondents using random sampling techniques. The data obtained were then analyzed using thetest chi square. Results: the results of the study showed that there was a significant relationship between service waiting time and the attitude of the officers in the service at the Pharmacy Installation with the level of satisfaction felt. Waiting time for services at Depo 1 Pharmacy is not in accordance with the Standard Minimum Procedure that has been determined. Conclusion: the waiting time and attitude of the officers have a significant relationship to patient satisfaction.